2006
DOI: 10.1016/j.jengtecman.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling market information processing in new product development: An empirical analysis

Abstract: This research explores the antecedents and consequences of market information processing during the development process of new high-tech products. To this end, we develop and test a conceptual model for market information processing in three generic stages of the new product development (NPD) process (predevelopment, development and commercialization). In addition, we explore the relationships between market information processing, its antecedents, and product advantage and success. We test our model with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 79 publications
(73 reference statements)
2
102
1
3
Order By: Relevance
“…To Veldhuizen, Hultink and Griffin (2006), the Market Orientation is achieved through the processing of the market information, since several studies on the use of market information have confirmed its positive relationship with the successful development of new products. However, information processing is considered a difficult field to manage, because many organizations fail to effectively absorb market information on new products (OTTUM; MOORE, 1997;VELDHUIZEN;GRIFFIN, 2006).…”
Section: The Processing Of Market Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…To Veldhuizen, Hultink and Griffin (2006), the Market Orientation is achieved through the processing of the market information, since several studies on the use of market information have confirmed its positive relationship with the successful development of new products. However, information processing is considered a difficult field to manage, because many organizations fail to effectively absorb market information on new products (OTTUM; MOORE, 1997;VELDHUIZEN;GRIFFIN, 2006).…”
Section: The Processing Of Market Informationmentioning
confidence: 99%
“…However, information processing is considered a difficult field to manage, because many organizations fail to effectively absorb market information on new products (OTTUM; MOORE, 1997;VELDHUIZEN;GRIFFIN, 2006). Ottum and Moore (1997) consider that the success or failure of the organization's new products is connected to the competence of the organization in the processing of market information, namely, the generation, dissemination and use of market information.…”
Section: The Processing Of Market Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this element of CRM can develop the strategies of the organization in order to satisfy customer needs. Accordingly, a study by Veldhuizen et al [39] attested to the effective role of market information processing in new product advantage and success through the new product development process. Effective information processing has been known as a challenging area because many organizations are not able to utilize market information in their NPD process [58].…”
Section: Analytical Crm and New Product Developmentmentioning
confidence: 99%